QUANTITATIVE SELECTION COA, PAN-SH, PAK DURING HYPOXIA CONFINED SPACE-BASED ION-EXCHANGE CHROMATOGRAPHY - Сальникова, Н.В. (World of Medicine and Biology, 2015)
Hypoxia confined space (GSP) leads to increased levels of Pantothenic acid in the liver and blood. During the preliminary injection PAK-Ca also increasing Pantothenic acid in the blood and liver.